Effect of oral glucose tolerance test-based insulin resistance on embryo quality in women with/without polycystic ovary syndrome - Hu, Zhengyan; Zeng, Rujun; Tang, Yuanting; Liao, Yingjun; Li, Tao; Qin, Lang (Frontiers in Endocrinology, 2024)
Objective: To explore the effects of insulin resistance (IR) on embryo quality and pregnancy outcomes in women with or without polycystic ovary syndrome (PCOS) undergoing in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI). Methods: A retrospective cohort study concerning patients with/without PCOS who received gonadotropin-releasing hormone (GnRH)antagonist protocol for IVF/ICSI from January 2019 to July 2022 was conducted. All the patients included underwent oral glucose tolerance test plus the assessment of insulin release within 6 months before the controlled ovarian stimulation. The Matsuda Index was calculated to diagnose IR. Two populations (PCOS and non-PCOS) were included and each was divided into IR and non-IR groups and analyzed respectively. The primary outcome was the high-quality day 3 embryo rate. Results: A total of 895 patients were included (751 with PCOS and 144 without PCOS). For patients with PCOS, the IR group had a lower high-quality day 3 embryo rate (36.8% vs. 39.7%, p=0.005) and available day 3 embryo rate (67.2% vs. 70.6%, p<0.001). For patients without PCOS, there was no significant difference between the IR and non-IR groups in high-quality day 3 embryo rate (p=0.414) and available day 3 embryo rate (p=0.560). There was no significant difference in blastocyst outcomes and pregnancy outcomes for both populations. Conclusion: Based on the diagnosis by the Matsuda Index, IR may adversely affect the day 3 embryo quality in patients with PCOS but not pregnancy outcomes. In women without PCOS, IR alone seems to have less significant adverse effects on embryo quality than in patients with PCOS. Better-designed studies are still needed to compare the differences statistically between PCOS and non-PCOS populations.